2017
DOI: 10.24071/llt.2017.200202
|View full text |Cite
|
Sign up to set email alerts
|

Empowering English Writing Students: Reflecting on Aspects of the Process That Helped Me Most?

Abstract: Process-oriented writing instruction has been advocated for both L1 and L2 writing classrooms since the 1960s. Empowering learner autonomy may best occur through non-direct instruction (Rogers & Freiberg, 1994), engaging students in social learning (Vygotsky, 1978) and creating workshop-like classrooms (Murray, 2004). Any number of techniques can be used, preferably in-sync with each other, to accomplish such an approach. This study will examine the results of some recent action research in the classroom to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Furthermore, providing feedback to the students could enhance their grammatical skills (Westmacott, 2017) and boost their motivation to write better (Hamidun, Hizwari, & Othman, 2013;Zarei, Ahour, & Seifoori, 2020). In terms of psychological implication, it could increase the students' morale because it showed that the teacher checked their essay thoroughly (Glenn & Goldthwaite, 2014;Walker, 2017). This could improve their writing skills when the teacher drew attention to inaccuracies in their writing and asked follow-up questions regarding their points (Saidon, Said, Soh, & Husnin, 2018).…”
Section: Literature Review Corrective Feedback On Writingmentioning
confidence: 99%
“…Furthermore, providing feedback to the students could enhance their grammatical skills (Westmacott, 2017) and boost their motivation to write better (Hamidun, Hizwari, & Othman, 2013;Zarei, Ahour, & Seifoori, 2020). In terms of psychological implication, it could increase the students' morale because it showed that the teacher checked their essay thoroughly (Glenn & Goldthwaite, 2014;Walker, 2017). This could improve their writing skills when the teacher drew attention to inaccuracies in their writing and asked follow-up questions regarding their points (Saidon, Said, Soh, & Husnin, 2018).…”
Section: Literature Review Corrective Feedback On Writingmentioning
confidence: 99%